Pengaruh Kesadaran Wajib Pajak, Pemeriksaan Pajak Dan Penagihan Pajak Terhadap Penerimaan Pajak Penghasilan Badan Pada Kantor Pelayanan Pajak (KPP) Pratama Metro - Saketi, Via Dewi; Zanaria, Yulita; Kurniawan, Angga (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to analyze Taxpayer Awareness (1), Tax Audit (2), Tax Collection (3) on Corporate Income Tax Receipts at the Tax Service Office (KPP) Pratama Metro. The population in this study were 94 respondents.The data collection technique in this study used a saturated sampling. This method is where all the population is sampled. The data in this study used SPSS version 26 with multiple linear regression analysis testing. The results of this study indicate that Taxpayer Awareness, Tax Audit, Tax Collection have partial or simultaneous effect on Corporate Income Tax Receipts at the Tax Service Office (KPP) Pratama Metro